Implikasi Metafisika Intersubjektif Armada Riyanto dalam Tradisi Belis Budaya Manggarai - Dial, Martina (Department of Language and Literature, Faculty of Cultural Studies, Universitas Brawijaya, 2025)
This study examines the relationship between Armada Riyanto's intersubjective metaphysics and the belis tradition in Manggarai culture. The belis tradition, which has been understood as a social and economic practice in marriage customs, is reexamined philosophically as a relational event that reveals the essence of human existence as beings who “are-with” (being-with). Using a qualitative-philosophical approach through literature study and hermeneutic analysis, this study interprets the symbolic, social, and existential meanings of belis within the framework of Riyanto's intersubjective metaphysics. Riyanto's thinking, which is based on a synthesis of phenomenology (Husserl, Heidegger), the ethics of alterity (Levinas), and personalist dialogue (Buber), asserts that intersubjective relations are not merely a social aspect, but the ontological basis of human existence. The results of the study show that the practice of belis in Manggarai society reflects the principles of relationality, recognition, and responsibility between subjects. The symbolic gift-giving between the male and female families not only strengthens social relationships but also affirms the dignity and existence of both parties. This tradition reflects metaphysical praxis in which humans affirm each other through love and solidarity. Furthermore, the ecological and spiritual dimensions of belis reveal the interconnectedness of humans with nature and the Transcendent, as emphasized in Riyanto's concept of cosmic relations.